การออกแบบเรขศิลป์สำหรับผลิตภัณฑ์ไลฟ์สไตล์ของชุมชนทอผ้าฝ้ายลาวครั่ง อำเภอบ้านไร่ จังหวัดอุทัยธานี โดยใช้กลยุทธ์การตลาดโชคลาง - เลอลักษณ์ ศรีเกษมศิรา (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were to 1) study and analyze Laos-Krang cotton wisdom of Banrai District, Uthai-Thani Province,  to use in graphic design for new lifestyle products; 2) expand a new market for new lifestyle products, by using Blue Ocean Strategy; 3) explor guidelines for graphic design using Superstitious Marketing Strategy. The samples were composed of one community  Development Officer specializing in Banrai District, Uthai-Thani Province; one Key Informant, 23 Laos-Krang cotton weaving group leaders in Banrai District, Uthai-Thani Province; three highly experienced designers with expertise in branding and Marketing (by means of Purposive and Snowball Sampling), and a target group, Thai Generation Y (by means of Accident and Snowball Sampling). The sample size of 400 Thai Generation Y for earch of three questionnaires was determined by using Yamane s formula of sample size with a confidence coefficient of 95% (Yamane, 1967); and 133, 210, and 214 samples for first, second and third questionnaires were completely collected respectively over the specified period of time. The research was conducted using Mixed Methodology, led by Qualitative research and followed by Quantitative Research. The Qualitative data were collected by  field researches, applied Delphi methods, in-depth interview, focus group, discussions, observations and photographing; and were analyzed and synthesized by categorizing the findings for use as design elements. Furthermore, the research instruments used in collecting the Quantitative data were three I.O.C. assessed questionnaires with the scores 0.64, 0.90, and 1.0 in order. These questionnaires were for a target group, Thai Generation Y (born between 1982-1995), to vote for the final brand name, the final product design direction, and the final logo separately. The quantitative data were analyzed by using the descriptive  statistics of arithmetic mean and standard deviation. Moreover, the three sets of research results answering the three research objectives were as follows: Firstly, Laos-Krang Cotton wisdom of Banrai District, Uthai-Thani Province, for use in graphic design for new lifestyle product design were 1) the three categories of Jok pattern corresponding to the superstition, and 2) the fluorescent color scheme of Jok pattern. Next, follow the guidelines for graphic design using  superstitious marketing strategies. However, the key point of this research was a new body of knowledge including a guideline for the development of community cultural Lifestyle product using concepts of local culture wisdom and markrting trend, which can be used as a guideline for entrepreneurs in Southease Asia including Thailand, to apply for their communities with indigenous wisdom of other cultures. Last but not  least, the successfull  application  of the new body of knowledge to any community requires a Community Participation Process (Disatapundhu and others. 2019) in three main steps respectively, which are 1) Attitude, 2) Understanding and Knowledge and 3) Hands-on experiences.